HUBUNGAN PERSEPSI SISWA TERHADAP MOTIVASI DENGAN HASIL BELAJAR IPA KELAS VIII MTS MASMUR - Miranda Sari, Dwi; Suryanti (Jurnal Biogenerasi, 2023)
The purpose of this study was to determine the relationship between motivation and learning outcomes in science class VIII at MTs Masmur Pekanbaru in the 2022/2023 academic year. This research is a quantitative research using correlational method. The population in this study were all students of class VIII MTs Masmur Pekanbaru with a total of 68 students. The sample in this study is the entire population using saturated sample technique. Data collection techniques using observation, interviews, questionnaires and documentation. The results showed that there was a significant relationship between learning motivation and science learning outcomes for class VIII students at MTs Masmur Pekanbaru in the 2022/2023 academic year with a correlation of 0.705 and being in the strong or high criteria.